Determinants of cassava distribution in Nigeria - Ugwu, B.; Nweke, F. (Elsevier, 1996)
Smallholder farmers in Nigeria cultivate numerous staple crops, either as sole crops or in crop mixtures. The distribution of cassava is discussed in terms of its importance relative to eight other major staples. As a result of the criteria associated with its definition, the relative importance of a crop was based on three concepts; two are field area and the third is farmers' ordinal crop rank. To delineate its determinants, the relative importance of cassava based on each of the above three concepts was regressed as a function of environment, occurrence of famine, demographic and market variables, in an ordinary least squares regression framework. The results show that ecological and non-ecological factors determine cassava's relative importance, especially on a field area basis. The occurrence of famine is also an important determinant, but only on a farmers' ordinal crop rank basis. In general, non-ecological factors are more important determinants of the relative importance of cassava in Nigeria than ecological factors.